Thermoelectric conversion materials and thermoelectric conversion elements

By adsorbing organic semiconductors with specific structures on the conductive material, the problem of difficult to take into account both the Seebeck coefficient and the conductivity of the existing thermoelectric conversion material is solved, and an efficient and low-cost thermoelectric conversion material is achieved, which is suitable for non-planar thermoelectric components.

JP7655158B2Active Publication Date: 2025-04-02TOYO INK MFG CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021144998
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-06
Publication Date
2025-04-02
Estimated Expiration
2041-09-06

AI Technical Summary

Technical Problem

The existing thermoelectric conversion materials have a difficult time to take into account both the Seebeck coefficient and the conductivity, and contain rare elements or harmful substances, making it complex and expensive, making it difficult to form non-planar thermoelectric components.

Method used

The thermoelectric conversion material containing the conductive material A and the organic semiconductor B of a specific structure is used to manufacture the thermoelectric conversion element by adsorbing a diaryl azo-based structure on the surface of the conductive material to improve the Seebeck coefficient and conductivity, and printable technology is used.

Benefits of technology

The balance of high Seebeck coefficient and conductivity is achieved, reducing manufacturing energy consumption and cost, and is suitable for non-planar thermoelectric components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007655158000001
    Figure 0007655158000001
  • Figure 0007655158000002
    Figure 0007655158000002
  • Figure 0007655158000003
    Figure 0007655158000003
Patent Text Reader

Abstract

To provide a thermoelectric conversion material that compatibly attains an excellent Seebeck coefficient and conductivity, and has a high power factor.SOLUTION: A thermoelectric conversion material contains a conductive material A and an organic semiconductor B, which is a compound expressed by general formula (1) or (2). In the formula, Ar1, Ar2, Ar3, Ar5 represent a phenyl group or naphthyl group which may be substituted by a substituent, and Ar4 represents a phenylene group which may be substituted by a substituent. The substituents are a halogen atom, a cyano group, a nitro group, a hydroxy group, a carboxy group, an alkyl group, an alkoxy group, an aryloxy group, an alkylthio group, an arylthio group, an aryl group, a heterocyclic group, an amino group, a formyl group, and -SO3M. Here, M is a metal atom. In Ar2 and Ar5, at least one hydrogen atom on carbon atoms adjacent to a carbon atom bonded to an azo group is substituted by any of the hydroxy group, alkoxy group and amino group.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a thermoelectric conversion material and a thermoelectric conversion element. [Background technology]

[0002] Thermoelectric materials, which can convert thermal energy into electrical energy and vice versa, are used in thermoelectric conversion elements such as thermoelectric generators and Peltier elements. Thermoelectric conversion elements are elements that convert heat into electrical power and are made up of a combination of semiconductors and metals. Typical thermoelectric conversion elements are classified into p-type semiconductors alone, n-type semiconductors alone, and combinations of p-type and n-type semiconductors. Thermoelectric conversion elements utilize the Seebeck effect, which generates an electromotive force when heat is applied to create a temperature difference between the two ends of a semiconductor. To achieve a larger potential difference, thermoelectric conversion elements generally use a combination of p-type and n-type semiconductors as materials.

[0003] Thermoelectric conversion elements are also used as thermoelectric modules, which are made by combining a large number of elements in a plate or cylindrical shape. They can directly convert thermal energy into electricity, and can be used, for example, as a power source for wristwatches that operate using body heat, and for terrestrial and satellite power generation. The performance of a thermoelectric conversion element depends on the performance of the thermoelectric conversion material and the durability of the module.

[0004] As described in Non-Patent Document 1, the dimensionless thermoelectric figure of merit (ZT) is used as an index representing the performance of a thermoelectric conversion material. In addition, the power factor PF (=S 2 ·σ) may also be used. The dimensionless thermoelectric figure of merit "ZT" is expressed by the following formula (1). ZT=(S 2 σ T) / κ Equation (1) where S is the Seebeck coefficient (V / K), σ is the electrical conductivity (S m), T is the absolute temperature (K), and κ is the thermal conductivity (W / (m K)). The thermal conductivity κ is expressed by the following equation (2): κ=α·ρ·C···Equation (2) where α is the thermal diffusivity (m 2 / s), ρ is the density (kg / m 3 ), and C is the specific heat capacity (J / (kg·K)). That is, in order to improve the thermoelectric conversion performance (hereinafter also referred to as thermoelectric properties), it is important to improve the Seebeck coefficient or electrical conductivity while decreasing the thermal conductivity.

[0005] Typical thermoelectric conversion materials include inorganic materials such as bismuth-tellurium (Bi-Te) systems from room temperature to 500K, lead-tellurium (Pb-Te) systems from room temperature to 800K, and silicon-germanium (Si-Ge) systems from room temperature to 1000K.

[0006] However, thermoelectric conversion materials containing these inorganic materials often contain rare elements, making them expensive, or may contain hazardous substances. Furthermore, inorganic materials are difficult to process, making the manufacturing process complicated. Therefore, thermoelectric conversion materials containing inorganic materials require high manufacturing energy and cost, making them difficult to generalize. Furthermore, because inorganic materials are rigid, it is difficult to form flexible thermoelectric conversion elements that can be installed on non-planar shapes.

[0007] In response to this, research is underway into thermoelectric conversion elements that use organic materials instead of conventional inorganic materials. Organic materials have excellent moldability and are more flexible than inorganic materials, making them highly versatile within the temperature range in which they do not decompose. Furthermore, because printing techniques can be easily utilized, they are more advantageous than inorganic materials in terms of manufacturing energy and costs.

[0008] For example, Patent Document 1 describes a thermoelectric material in which an organic dye skeleton is bonded to a polymer dispersant and contained together with carbon nanotubes (CNTs), thereby achieving good CNT dispersibility, suitability for coating methods, and excellent thermoelectric power. Patent Document 2 also describes a thermoelectric conversion material in which a porphyrin skeleton is bonded to a substituent containing an alkyl group, and which exhibits a high Seebeck coefficient. However, in the invention of Patent Document 1, the polymer chain of the polymer dispersant inhibits interaction with the CNTs, and sufficient performance is not obtained. In addition, in the invention of Patent Document 2, the conductivity is 10 -8 ~10 -7 The value is low at S / cm, and it is not possible to obtain a practical value for a thermoelectric element. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] International Publication No. 2015 / 050113 [Patent Document 2] International Publication No. 2015 / 129877 [Non-patent literature]

[0010] [Non-Patent Document 1] Takenobu Kajikawa, "Thermoelectric Conversion Technology Handbook (First Edition)", NTS Publishing, p.19 Summary of the Invention [Problem to be solved by the invention]

[0011] The problem to be solved by the present invention is to provide a thermoelectric conversion material that achieves both a good Seebeck coefficient and good electrical conductivity and exhibits a high power factor, and also to provide a thermoelectric conversion element that exhibits excellent thermoelectric performance. [Means for solving the problem]

[0012] The present inventors have conducted extensive research to solve the above problems and have arrived at the present invention. That is, the present invention relates to a thermoelectric conversion material containing a conductive material A and an organic semiconductor B, wherein the organic semiconductor B is a compound represented by the following general formula (1) or (2).

[0013] [ka]

[0014] [In general formulas (1) and (2), Ar1, Ar2, Ar3, and Ar5 each represent a phenyl group optionally substituted with the following substituents, or a naphthyl group optionally substituted with the following substituents. Ar4 represents a phenylene group optionally substituted with the following substituents. The substituents are a halogen atom, a cyano group, a nitro group, a hydroxyl group, a carboxyl group, a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkoxy group, an aryloxy group, a substituted or unsubstituted alkylthio group, an arylthio group, a substituted aryl group, a heterocyclic group, a substituted or unsubstituted amino group, a formyl group, and -SO3M. M represents a metal atom. However, in Ar2 and Ar5, at least one hydrogen atom on the carbon atom adjacent to the carbon atom bonded to the azo group is substituted with a hydroxyl group, a substituted or unsubstituted alkoxy group, or a substituted or unsubstituted amino group.]

[0015] The present invention also relates to the above thermoelectric conversion material, wherein the organic semiconductor B is a compound represented by any one of the following general formulas (3) to (5).

[0016] [ka]

[0017] [In general formulas (3) to (5), X represents a hydroxyl group, a substituted or unsubstituted alkoxy group, or a substituted or unsubstituted amino group. The hydrogen atoms in general formulas (3) to (5) may be substituted with the following substituents. The substituents are each independently a halogen atom, a cyano group, a nitro group, a hydroxyl group, a carboxy group, a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkoxy group, an aryloxy group, a substituted or unsubstituted alkylthio group, an arylthio group, a substituted aryl group, a heterocyclic group, a substituted or unsubstituted amino group, a formyl group, or -SO3M. M represents a metal atom.]

[0018] The present invention also relates to the above thermoelectric conversion material, wherein the content of the organic semiconductor B is 10 to 200 mass % relative to the total amount of the conductive material A.

[0019] The present invention also relates to a thermoelectric conversion element having a thermoelectric conversion film made of the above thermoelectric conversion material and electrodes, the thermoelectric conversion film and the electrodes being electrically connected to each other. [Effects of the Invention]

[0020] The present invention can provide a thermoelectric conversion material that achieves both a good Seebeck coefficient and good electrical conductivity, and can also provide a thermoelectric conversion element that exhibits excellent thermoelectric performance. DETAILED DESCRIPTION OF THE INVENTION

[0021] <Thermoelectric conversion materials> The thermoelectric conversion material of the present invention is characterized by containing a conductive material A and an organic semiconductor B having a specific structure. Hereinafter, embodiments of the present invention will be described in detail.

[0022] <Conductive material A> The conductive material A contributes to improving conductivity. Examples of the conductive material A include conductive carbon materials, metal materials, conductive polymers, etc. Examples of carbon materials include graphite, carbon nanotubes, Ketjen black, graphene nanoplates, and graphene. Examples of metal materials include metal powders such as gold, silver, copper, nickel, chromium, palladium, rhodium, ruthenium, indium, silicon, aluminum, tungsten, molybdenum, germanium, gallium, and platinum, as well as alloys and composite powders of ZnSe, CdS, InP, GaN, SiC, and SiGe. Also included are fine particles having a core coated with a material different from the core material, specifically, for example, silver-coated copper powder, which has a copper core and a silver-coated surface. Other examples include powders of metal oxides such as silver oxide, indium oxide, tin oxide, zinc oxide, ruthenium oxide, ITO (tin-doped indium oxide), AZO (aluminum-doped zinc oxide), and GZO (gallium-doped zinc oxide), as well as powders surface-coated with these metal oxides. Examples of conductive polymers include PEDOT / PSS (a composite of poly(3,4-ethylenedioxythiophene) (PEDOT) and polystyrene sulfonic acid (PSS)), polyaniline, polyacetylene, polypyrrole, polythiophene, and polyparaphenylene. The conductive material A may be one type or a combination of two or more types.

[0023] The shape of the conductive material A is not particularly limited, and amorphous, aggregated, scale-like, microcrystalline, spherical, flake-like, wire-like, etc. may be used as appropriate.

[0024] From the viewpoint of achieving both a high Seebeck coefficient and high electrical conductivity, at least one selected from the group consisting of carbon nanotubes, Ketjen black, graphene nanoplates, and graphene is preferred, more preferably carbon nanotubes, and particularly preferably single-walled carbon nanotubes.

[0025] Examples of the conductive material A include flake graphite such as CMX, UP-5, UP-10, UP-20, UP-35N, CSSP, CSPE, CSP, CP, CB-150, CB-100, ACP, ACP-1000, ACB-50, ACB-100, ACB-150, SP-10, SP-20, J-SP, SP-270, HOP, GR-60, LEP, F#1, and Examples of graphite include F#2, F#3, BF-3AK, FBF, BF-15AK, CBR, CPB-6S, CPB-3, 96L, 96L-3, K-3, SC-120, SC-60, HLP, CP-150, and SB-1 manufactured by Chuetsu Graphite Industries Co., Ltd., EC1500, EC1000, EC500, EC300, EC100, and EC50 manufactured by Ito Graphite Industries Co., Ltd., and 10099M and PB-99 manufactured by Nishimura Graphite Co., Ltd. Examples of spherical natural graphite include CGC-20, CGC-50, CGB-20, and CGB-50 manufactured by Nippon Graphite Industries Co., Ltd. Examples of amorphous graphite include Blue P, AP, AOP, and P#1 manufactured by Nippon Graphite Industries Co., Ltd., and APR, K-5, AP-2000, AP-6, 300F, and 150F manufactured by Chuetsu Graphite Co., Ltd. Examples of artificial graphite include PAG-60, PAG-80, PAG-120, PAG-5, HAG-10W, and HAG-150 manufactured by Nippon Graphite Industries Co., Ltd.; G-4AK, G-6S, G-3G-150, G-30, G-80, G-50, SMF, EMF, SFF, SFF-80B, SS-100, BSP-15AK, BSP-100AK, and WF-15C manufactured by Chuetsu Graphite Co., Ltd.; and SGP-100, SGP-50, SGP-25, SGP-15, SGP-5, SGP-1, SGO-100, SGO-50, SGO-25, SGO-15, SGO-5, SGO-1, SGX-100, SGX-50, SGX-25, SGX-15, SGX-5, and SGX-1 manufactured by SEC Carbon Co., Ltd.Examples of commercially available carbon black include Tokablack #4300, #4400, #4500, and #5500 manufactured by Tokai Carbon Co., Ltd., Printex L manufactured by Degussa Corporation, and Raven 7000, 5750, 5250, 5000ULTRAIII, 5000ULTRA, Conductex SC ULTRA, and Conductex 975 manufactured by Colombian. Furnace blacks such as ULTRA, PUERBLACK 100, 115, and 205; Mitsubishi Chemical Corporation's #2350, #2400B, #2600B, #3050B, #3030B, #3230B, #3350B, #3400B, and #5400B; Cabot Corporation's MONARCH 1400, 1300, and 900, Vulcan XC-72R, and BlackPearls 2000; and Timcal Corporation's Ensaco 250G, Ensaco 260G, Ensaco 350G, and Super P-Li; Ketjen blacks such as Lion Corporation's EC-300J and EC-600JD; and acetylene blacks such as Denka Black, Denka Black HS-100, and FX-35, all of which are manufactured by Denki Kagaku Kogyo Co., Ltd. Examples of commercially available conductive carbon fibers and carbon nanotubes include vapor grown carbon fibers such as VGCF manufactured by Showa Denko K.K., single-walled carbon nanotubes such as EC1.5 and EC1.5-P manufactured by Meijo Nano Carbon Co., Ltd., TUBALL manufactured by Kusumoto Chemicals Co., Ltd., and ZEONANO manufactured by Zeon Nano Technology Inc., FloTube9000, FloTube7000, and FloTube2000 manufactured by CNano, NC7000 manufactured by Nanocyl, and 100T and 200P manufactured by CNano. These are not particularly limited, and can be used alone or in combination of two or more types.

[0026] <Organic Semiconductor B> Organic semiconductor B has a structure represented by general formula (1) or (2). The diarylazo skeleton portion in general formula (1) is believed to improve thermoelectric conversion performance by adsorbing to the surface of conductive material A. For improved thermoelectric conversion performance, organic semiconductor B preferably has a structure having two azo groups in the molecule, as represented by general formula (2).

[0027] The organic semiconductor B contributes to improving the Seebeck coefficient in the thermoelectric conversion material. From the viewpoint of achieving both a high Seebeck coefficient and high electrical conductivity, the content of the organic semiconductor B is preferably 10 to 200 mass % and more preferably 25 to 150 mass % relative to the total amount of the conductive material A.

[0028] Furthermore, in order to promote surface adsorption and uniformity to the conductive material A and further increase the molecular ratio, it is preferable that the molecular weight of the organic semiconductor B is small. The upper limit of the molecular weight is preferably 2,000 or less, more preferably 1,000 or less. The lower limit is not particularly limited, but is generally 197 or more.

[0029] In organic semiconductor B, in Ar2 and Ar5, at least one hydrogen atom on the carbon atom adjacent to the carbon atom bonded to the azo group is preferably substituted with a hydroxyl group, a substituted or unsubstituted alkoxy group, or a substituted or unsubstituted amino group. By substituting the hydrogen atom on the carbon atom adjacent to the carbon atom bonded to the azo group with these functional groups, conjugation is extended due to the interaction between the azo group and these functional groups, and improvement in thermoelectric conversion performance due to the interaction with conductive material A can be expected. In Ar2 and Ar5, it is more preferable that the hydrogen atom on the carbon atom adjacent to the carbon atom bonded to the azo group be substituted with a hydroxyl group or a substituted or unsubstituted amino group.

[0030] The phenyl or naphthyl group in Ar1, Ar2, Ar3, Ar4, and Ar5 may be substituted with a halogen atom, a cyano group, a nitro group, a hydroxyl group, a carboxy group, a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkoxy group, an aryloxy group, a substituted or unsubstituted alkylthio group, an arylthio group, a substituted aryl group, a heterocyclic group, a substituted or unsubstituted amino group, a formyl group, or -SO3M (M is a metal atom). The metal atom represented by M is preferably an alkali metal. Examples of alkali metals include lithium, sodium, and potassium.

[0031] The aforementioned substituted alkyl group, substituted alkoxy group, substituted alkylthio group, substituted aryl group, and substituted amino group refer to an alkyl group, alkoxy group, alkylthio group, aryl group, or amino group substituted with an alkyl group, hydroxyl group, alkoxy group, amino group, carboxyl group, halogen, nitro group, or cyano group.

[0032] The organic semiconductor B is preferably a compound represented by any one of general formulas (3) to (5). The groups in general formulas (3) to (5) have the same meanings as the groups in general formula (1) or (2).

[0033] <Other ingredients> The thermoelectric conversion material of the present invention may contain other components as needed to improve its properties. For example, by containing the other components exemplified below, it is possible to further improve the coatability, electrical conductivity, and thermoelectric properties.

[0034] (organic semiconductors other than organic semiconductor B) The thermoelectric conversion material of the present invention may contain an organic semiconductor other than organic semiconductor B. The organic semiconductor other than organic semiconductor B is not particularly limited, but examples thereof include phenylthiazolothiazole other than organic semiconductor B and derivatives thereof, perylene and derivatives thereof, and diketopyrrolopyrrole and derivatives thereof.

[0035] (solvent) The solvent may be used as a solvent or dispersion medium for uniformly mixing the conductive material A and the organic semiconductor B. The solvent that can be used is not particularly limited as long as it can dissolve or disperse the conductive material A and the organic semiconductor B, and examples of the solvent that can be used include organic solvents and water, and two or more of them may be used in combination. The organic solvent may be appropriately selected as needed from, for example, alcohols such as methanol, ethanol, propanol, butanol, ethylene glycol methyl ether, diethylene glycol methyl ether, terpineol, dihydroterpineol, 2,4-diethyl-1,5-pentanediol, 1,3-butylene glycol, and isobornylcyclohexanol; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ethers such as tetrahydrofuran, dioxane, ethylene glycol dimethyl ether and diethylene glycol dimethyl ether; aliphatic hydrocarbons such as hexane, heptane, and octane; aromatic hydrocarbons such as benzene, toluene, xylene, and cumene; esters such as ethyl acetate and butyl acetate; and N-methylpyrrolidone. N-methylpyrrolidone is particularly preferred as the solvent.

[0036] (auxiliary agent) Usable auxiliary agents are not particularly limited, and examples thereof include lactams, alcohols, amino alcohols, carboxylic acids, acid anhydrides, and ionic liquids. Specific examples are as follows: Lactams: pyrrolidone, caprolactam, N-methylcaprolactam, N-octylpyrrolidone, and the like. Alcohols: sucrose, glucose, fructose, lactose, sorbitol, mannitol, xylitol, glycerin, polyethylene glycol, polypropylene glycol, trifluoroethanol, m-cresol, thiodiglycol, and the like. Amino alcohols: diethanolamine, triethanolamine, etc. Carboxylic acids: 2-furancarboxylic acid, 3-furancarboxylic acid, dichloroacetic acid, trifluoroacetic acid, and the like. Acid anhydrides: acetic anhydride, propionic anhydride, acrylic anhydride, methacrylic anhydride, benzoic anhydride, succinic anhydride, maleic anhydride, itaconic anhydride, glutaric anhydride, phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride (also known as cyclohexane-1,2-dicarboxylic anhydride), trimellitic anhydride, hexahydrotrimellitic anhydride, pyromellitic anhydride, himic anhydride, biphenyltetracarboxylic anhydride, 1,2,3,4-butanetetracarboxylic anhydride, naphthalenetetracarboxylic anhydride, and 9,9-fluorenylidenebisphthalic anhydride, etc. Copolymers of maleic anhydride copolymerized with other vinyl monomers, such as styrene-maleic anhydride copolymer, ethylene-maleic anhydride copolymer, isobutylene-maleic anhydride copolymer, and alkyl vinyl ether-maleic anhydride copolymer.

[0037] From the viewpoint of electrical conductivity and thermoelectric properties, it is preferable to use at least one of lactams and alcohols as the auxiliary. The content of the auxiliary is preferably in the range of 0.1 to 30 mass%, more preferably in the range of 1 to 10 mass%, and even more preferably in the range of 1 to 5 mass%, based on the total mass of the thermoelectric conversion material. By making the content of the auxiliary 0.1 mass% or more, it is possible to easily obtain the effect of improving electrical conductivity and thermoelectric properties. Furthermore, when the content of the auxiliary is 50 mass% or less, it is possible to suppress deterioration of film properties.

[0038] (resin) The thermoelectric conversion material of the present invention may contain a resin to the extent that it does not affect the electrical conductivity and thermoelectric properties, for the purpose of adjusting the film formability and film strength. The resin is preferably one that is compatible with or uniformly dispersible in each component of the thermoelectric conversion material. Either a thermosetting resin or a thermoplastic resin may be used. Specific examples of usable resins include polyester resins, polyimide resins, polyamide resins, fluororesins, vinyl resins, epoxy resins, xylene resins, aramid resins, polyurethane resins, polyurea resins, melamine resins, phenolic resins, polyether resins, acrylic resins, acrylamide resins, and copolymer resins thereof. While not particularly limited, in one embodiment, it is preferable to use at least one resin selected from the group consisting of polyurethane resins, polyether resins, acrylic resins, and acrylamide resins.

[0039] <Thermoelectric conversion element> The thermoelectric conversion element of the present invention is characterized by being constructed using the above-described thermoelectric conversion material. In one embodiment, the thermoelectric conversion element has a thermoelectric conversion film formed using the above-described thermoelectric conversion material and electrodes, and the thermoelectric conversion film and the electrodes are electrically connected to each other. The thermoelectric conversion film is excellent in heat resistance and flexibility in addition to electrical conductivity and thermoelectric properties. Therefore, according to this embodiment, a high-quality thermoelectric conversion element can be easily realized.

[0040] The thermoelectric conversion film may be a film obtained by applying a thermoelectric conversion material to a substrate. Because thermoelectric conversion materials have excellent formability, it is easy to obtain a good film by application. A wet film-forming method is mainly used to form the thermoelectric conversion film. Specific examples include methods using various means such as spin coating, spraying, roller coating, gravure coating, die coating, comma coating, roll coating, curtain coating, bar coating, inkjet printing, dispenser printing, silk screen printing, and flexographic printing. An appropriate method can be selected from the above methods depending on the thickness to be applied, the viscosity of the material, and the like.

[0041] The thickness of the thermoelectric conversion film is not particularly limited, but is preferably formed to have a certain thickness or more so that a temperature difference can be generated and transmitted in the thickness direction or in the plane direction of the thermoelectric conversion film, as described below. In one embodiment, from the viewpoint of thermoelectric properties, the thickness of the thermoelectric conversion film is preferably in the range of 0.1 to 200 μm, more preferably in the range of 1 to 100 μm, and further preferably in the range of 1 to 50 μm.

[0042] Furthermore, the substrate to which the thermoelectric conversion material is applied may be a plastic film made of a material such as polyethylene, polyethylene terephthalate, polyethylene naphthalate, polyethersulfone, polypropylene, polyimide, polycarbonate, or cellulose triacetate, or glass.

[0043] In order to improve the adhesion between the substrate and the thermoelectric conversion film, various treatments can be performed on the surface of the substrate. Specifically, prior to application of the thermoelectric conversion material, UV ozone treatment, corona treatment, plasma treatment, or adhesion enhancing treatment may be performed.

[0044] The thermoelectric conversion element according to the embodiment of the present invention can be constructed by applying techniques well known in the art, except that it is constructed using the above-described thermoelectric conversion material. A more specific configuration of the thermoelectric conversion element and a manufacturing method thereof will be described as a representative example.

[0045] In one embodiment, the thermoelectric conversion element has a thermoelectric conversion film obtained using a thermoelectric conversion material and a pair of electrodes connected to the thermoelectric conversion film. Here, "electrically connected" means that they are joined to each other or can be electrically connected via other components such as wires.

[0046] The electrode material can be selected from metals, alloys, and semiconductors. In one embodiment, metals and alloys are preferred because they have high conductivity and low contact resistance with the thermoelectric conversion material according to the present invention that constitutes the thermoelectric conversion film. Specifically, the electrode preferably contains at least one material selected from the group consisting of gold, silver, copper, and aluminum. It is more preferred that the electrode contain silver.

[0047] The electrodes can be formed by methods such as vacuum deposition, thermocompression bonding of an electrode material foil or a film having an electrode material film, coating of a paste in which fine particles of the electrode material are dispersed, etc. From the viewpoint of process simplicity, methods using thermocompression bonding of an electrode material foil or a film having an electrode material film, and coating of a paste in which the electrode material is dispersed are preferred. [Example]

[0048] The present invention will be described in more detail below with reference to experimental examples, but is not limited to these examples. Unless otherwise specified, "parts" and "%" in the examples refer to "parts by mass" and "% by mass," respectively. Furthermore, "NMP" refers to N-methylpyrrolidone.

[0049] <Synthesis of organic semiconductor B> (Synthesis Example 1) 0.01 mol of 4-amino-4'-cyanobiphenyl was dissolved in 100 ml of a 50:50 volumetric water / acetone mixture (hereafter referred to as the water-acetone mixture) and stirred in an ice bath. 0.01 mol of sodium nitrite, 0.02 mol of concentrated hydrochloric acid, and 50 ml of the above mixture were added dropwise to this solution over 30 minutes. A mixture of 0.01 mol of 4-alkylphenol, 0.02 mol of sodium hydroxide, and 50 ml of the above mixture was then added dropwise to this solution over 30 minutes. The solution was stirred in the ice bath for 1 hour, and the precipitate was filtered to obtain the product (organic semiconductor B1).

[0050] (Synthesis Examples 2 to 9) Organic semiconductors B2 to B9 were obtained in the same manner as in Synthesis Example 1, except that 4-amino-4'-cyanobiphenyl was changed to a phenylamine shown in Table 1.

[0051] <Synthesis of dye-incorporated polymer> (Synthesis Example 10) With reference to paragraphs 0074 and 0075 of WO 2015 / 050113, a dye-introduced polymer was obtained, which was an acrylic polymer having a perylene skeleton introduced into the side chain and represented by the following structure, and had a mass-average molecular weight (Mw) of approximately 21,000.

[0052] [ka]

[0053] <Production of thermoelectric conversion materials> [Example 1] (Dispersion 1) 0.4 parts of single-walled carbon nanotubes "TUBALL" (abbreviated as SWCNT) manufactured by OCSiAl Corporation were weighed out as conductive material A, 0.4 parts of organic semiconductor B1 as organic semiconductor B, and 79.2 parts of NMP were weighed out and mixed. 140 parts of zirconia beads (φ1.25 mm) were then added, and the mixture was shaken in a Scandex for 2 hours. The zirconia beads were then removed by filtration, yielding dispersion liquid 1 of a thermoelectric conversion material.

[0054] [Examples 2 to 37, Comparative Examples 1 and 2] (Dispersions 2 to 37, comparative dispersions 1 to 2) Thermoelectric conversion material dispersions 2 to 37 and comparative dispersions 1 and 2 were obtained in the same manner as in Example 1, except that the type and amount of conductive material A and the type and amount of organic semiconductor B were changed as shown in Table 3.

[0055] The sources and abbreviations for the materials listed in the table are shown below. Graphite: Nippon Graphite Co., Ltd. graphite "CPB" MWCNT: Multi-walled carbon nanotube "100P" manufactured by Knano GNP: Graphene nanoplatelets "xGNP-M-5" manufactured by XGSciences Organic semiconductor B10, organic semiconductor B11, organic semiconductor B13, organic semiconductor B17, organic semiconductor B19, organic semiconductor B22, organic semiconductor B23, and organic semiconductor B28 were purchased from Tokyo Chemical Industry Co., Ltd. Organic semiconductor B12, organic semiconductor B14, organic semiconductor B15, organic semiconductor B16, organic semiconductor B18, organic semiconductor B20, organic semiconductor B21, organic semiconductor B24, organic semiconductor B25, organic semiconductor B26, organic semiconductor B27, and organic semiconductor B29 were purchased from Sigma-Aldrich Japan LLC.

[0056] <Evaluation of thermoelectric conversion materials> The obtained dispersions 1 to 35 and comparative dispersions 1 and 2 were each applied using an applicator to a 75 μm thick polyethylene terephthalate (PET) film sheet substrate, and then heated and dried at 120°C for 30 minutes to obtain a laminate having a 5 μm thick thermoelectric conversion film on the PET substrate. The electrical conductivity, Seebeck coefficient, and power factor (PF) of the obtained laminates having a thermoelectric conversion film (hereinafter also referred to as a coating film) were evaluated as follows. The results are shown in Table 3.

[0057] (conductivity) The obtained laminate was cut into a piece of 2.5 cm × 5 cm, and the resistivity was measured by the four-terminal method using a Loresta GX MCP-T700 (manufactured by Mitsubishi Chemical Analytech Co., Ltd.) in accordance with JIS-K7194. Then, the conductivity, which is the reciprocal of the resistivity, was calculated.

[0058] (Seebeck coefficient) The obtained laminate was cut into a piece of 3 mm × 10 mm, and a silver paste (REXALPHA RA FS 074, manufactured by Toyochem Co., Ltd.) was applied to 2 mm of each end of the cut laminate to create a thermoelectric conversion element. The Seebeck coefficient (μV / K) at 80°C was measured as the thermoelectric conversion performance using a ZEM-3LW manufactured by Advance Riko Co., Ltd.

[0059] (Power Factor (PF)) Using the obtained conductivity and Seebeck coefficient, the PF (=S 2σ) was calculated and evaluated according to the following criteria: PF is 2.5μW / (mK 2 ) or higher is a practical level. ◎: PF is 20μW / (mK 2 ) or better (very good) ○: PF is 10 μW / (mK 2 ) or more, 20μW / (mK 2 ) (good) △: PF is 2.5μW / (mK 2 ) or more, 10μW / (mK 2 ) (practical) ×: PF is 2.5 μW / (mK 2 ) (not practical)

[0060] [Table 1]

[0061] [Table 2]

[0062] [Table 3]

Claims

1. A thermoelectric conversion material comprising a conductive material A and an organic semiconductor B, wherein the conductive material A is at least one selected from the group consisting of graphite, carbon nanotubes, ketjen black, graphene nanoplates, and graphene, the organic semiconductor B is a compound represented by any one of organic semiconductors B1 to B29 below, and the content of the organic semiconductor B is 10 to 200 mass % with respect to the total amount of the conductive material A. 【Chemistry 1】

2. A thermoelectric conversion element comprising a thermoelectric conversion film made of the thermoelectric conversion material according to claim 1 and electrodes, the thermoelectric conversion film and the electrodes being electrically connected to each other.

Citation Information

Patent Citations

  • Conductive composition, conductive film using the composition, and manufacturing method thereof

    JP2013118166A

  • Thermoelectric conversion material and thermoelectric conversion element

    JP2015070250A

  • Aqueous inkjet yellow ink, ink set, and method for producing printed matter

    JP2020097738A

  • Thermoelectric conversion material and thermoelectric conversion element

    WO2015050113A1

  • Thermoelectric conversion material and thermoelectric conversion element

    WO2015129877A1